2017
DOI: 10.1002/pc.24688
|View full text |Cite
|
Sign up to set email alerts
|

Influence of magnetite nanoparticles on electrical, magnetic and thermal properties of chitin/cashew gum biopolymer nanocomposites

Abstract: In this study, we report the preparation of polymer blend nanocomposites based on chitin (CT)/cashew gum (CG) with various contents of magnetite nanoparticles (Fe3O4). The fabricated nanocomposites were characterised by FT infrared (FTIR), X‐ray diffraction (XRD), high‐resolution transmission electron microscopy (HRTEM), magnetic property (vibrating sample magnetometry (VSM)), differential scanning calorimetry (DSC), thermogravimetry (TGA) and impedance analyser. FTIR study revealed the characteristic absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…The absorption band at 558 and 450 cm −1 are assigned to the metal–oxygen vibrational modes of ZnFe 2 O 4 nanoparticles . The FTIR absorption signals of pure PIN are appeared at 3,419, 1,625, 1,456, 1,382, 1,118, and 752 cm −1 which is in accordance with our previous research . The major peak at 3,419 cm −1 is the characteristic N‐H stretching vibration of PIN.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The absorption band at 558 and 450 cm −1 are assigned to the metal–oxygen vibrational modes of ZnFe 2 O 4 nanoparticles . The FTIR absorption signals of pure PIN are appeared at 3,419, 1,625, 1,456, 1,382, 1,118, and 752 cm −1 which is in accordance with our previous research . The major peak at 3,419 cm −1 is the characteristic N‐H stretching vibration of PIN.…”
Section: Resultssupporting
confidence: 91%
“…. All the samples show a broad UV absorption peak at a lower wavelength region (π–π* transitions) and a weak shoulder at a higher wavelength region ( n –π* transitions) . The broad and weak UV absorption peaks of PIN are centered at 385 and 518 nm, respectively.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This observation is consistent with literature for chitin based composite. 26 The nano Fe-CNB used in this study exhibits magnetic behaviour in nature which is conrmed by the simple experiment of bringing a big magnet near the nano Fe-CNB powder. The experiment shows that under the inuence of the magnetic eld, the nano Fe-CNB particles are attracted to the big magnet.…”
Section: Thermal and Magnetic Behaviormentioning
confidence: 99%
“…Magnetic nanocomposite prepared by Fe3O4 nanoparticles and polystyrene can be used for microelectromechanical systems, since it shows good electrical conductivity [3]. The influence of magnetic nanoparticles was studied for chitin/cashew biopolymer composites, and the results revealed that an increase in thermal stability and the dielectric properties was improved due to the interaction with Fe3O4 nanoparticles [12]. Likewise, Fe3O4 nanoparticles/polymer composite was studied for polyvinyl butyral/magnetite (PVB/Fe3O4) and polymethylmethacrylate/magnetite (PMMA/Fe3O4) composites [13], pectin-magnetite nanocomposite [14], superparamagnetic iron oxide nanoparticles, graphene oxide, chitosan, and poly(vinyl alcohol) biocompatible polymers [15].…”
Section: Introductionmentioning
confidence: 99%